Histone methyltransferase SETD2 coordinates FACT recruitment with nucleosome dynamics during transcription - Carvalho, Sílvia (Oxford University Press, 2013)
Histone H3 of nucleosomes positioned on active genes is trimethylated at Lys36 (H3K36me3) by the SETD2 (also termed KMT3A/SET2 or HYPB) methyltransferase. Previous studies in yeast indicated that H3K36me3 prevents spurious intragenic transcription initiation through recruitment of a histone deacetylase complex, a mechanism that is not conserved in mammals. Here, we report that downregulation of SETD2 in human cells leads to intragenic transcription initiation in at least 11% of active genes. Reduction of SETD2 prevents normal loading of the FACT (FAcilitates Chromatin Transcription) complex subunits SPT16 and SSRP1, and decreases nucleosome occupancy in active genes. Moreover, co-immunoprecipitation experiments suggest that SPT16 is recruited to active chromatin templates, which contain H3K36me3-modified nucleosomes. Our results further show that within minutes after transcriptional activation, there is a SETD2-dependent reduction in gene body occupancy of histone H2B, but not of histone H3, suggesting that SETD2 coordinates FACT-mediated exchange of histone H2B during transcription-coupled nucleosome displacement. After inhibition of transcription, we observe a SETD2-dependent recruitment of FACT and increased histone H2B occupancy. These data suggest that SETD2 activity modulates FACT recruitment and nucleosome dynamics, thereby repressing cryptic transcription initiation.